Single versus tandem autologous stem-cell transplantation in patients with newly diagnosed multiple myeloma and high-risk cytogenetics. A retrospective, open-label study of the PETHEMA/Spanish Myeloma Group (GEM). Issue 14 (6th December 2022) - Villalba, Ana; Gonzalez-Rodriguez, Ana Pilar; Arzuaga-Mendez, Javier; Puig, Noemí; Arnao, Mario; Arguiñano, José María; Jimenez, María; Canet, Marta; Teruel, Ana I.; Sola, María; Díaz, Francisco J.; Encinas, Cristina; et al.
Abstract: Tandem ASCT has been suggested as a valid approach to improve the prognosis of patients with MM and HR cytogenetic. In this observational, retrospective study, 213 patients with newly diagnosed MM and HR cytogenetic in 35 hospitals from the Spanish Myeloma Group underwent single or tandem ASCT between January 2015 and December 2019 after induction with VTD/VRD. HR cytogenetic was defined as having ≥1 of the following: del17p, t (4;14), t (14;16) or gain 1q21. More patients in the tandem group had R-ISS 3 and >1 cytogenetic abnormality at diagnosis. With a median follow-up of 31 months (range, 10–82), PFS after single ASCT was 41 months versus 48 months with tandem ASCT ( p  = 0.33). PFS in patients with del17p undergoing single ASCT was 41 months, while 52% of patients undergoing tandem ASCT were alive and disease free at 48 months. In conclusion, tandem ASCT partly overcomes the bad prognosis of HR cytogenetic.